The Role of Connections Between Cellular and Tissue Mechanical Elements and the Importance of Applied Energy in Mechanotransduction in Cancerous Tissue - Frederick H. Silver (Biomolecules)
In the presence of cellular mutations and impaired mechanisms of energy transmission to the attached cells and tissues, excess energy is available to upregulate some of the mechanotransduction pathways that maintain cell and tissue structure and function. The ability to transfer applied energy through integrin-mediated pathways, cell ion channels, cell membrane, cytoskeleton–nucleoskeleton connections, cell junctions, and cell–extracellular matrix attachments provides an equilibrium for energy storage, transmission, and dissipation in tissues. Disruption in energy storage, transmission, or dissipation via genetic mutations blocks mechanical communication between cells and tissues and impairs the mechanical energy equilibrium that exists between cells and tissues. This results in local structural changes through altered regulatory pathways, which produce cell clustering, collagen encapsulation, and an epithelial–mesenchymal transition (EMT), leading to increased cellular motility along newly reorganized collagen fibers (fibrosis). The goal of this review is to postulate how changes in energy transfer between cells and the extracellular matrix may alter local energy equilibrium and mechanotransduction pathways. The changes along with cellular mutations lead to cell and ECM changes reported in cancer, which is postulated to modify mechanical equilibria between cells and their ECM. This leads to uncontrolled cancer cellular proliferation and collagen remodeling.